IMPLEMENTASI ALGORITMA RSA PADA SISTEM PENDUKUNG KEPUTUSAN PENGALOKASIAN DANA BANTUAN LANGSUNG MASYARAKAT DENGAN METODE WEIGHTED PRODUCT (STUDI KASUS DESA BEKA KECAMATAN MARAWOLA KABUPATEN SIGI) - Abdul Rahim (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
Immediate relief society is the Government's programme to reduce the poverty levels of society, by providing funds to the poor. However, often the assistance provided by the Government are not right on target in which the assistance should be devoted to the underprivileged community, but the community that are capable of in terms of material ever even get those funds in addition the process of implementation of assistance are still manual so need quite a long time and the purpose of the Government in reducing the level of poverty is not done properly. Based on the study of the literature undertaken obtained a decision support system that can address the problem of granting direct aid community and the method used is the Weighted Product method because it can work more effectively and efficiently than any other method. The results of this study indicate that a decision support system can address the issue of the direct recipient of the community that is still done manually and subjective in village Beka Sub Marawola tropospheric processes so Sigi Regency can faster and the RSA algorithm and propositions that are used to provide strong data security. Keywords : Cryptography, Rivest Shamir Adleman and (RSA), A Decision Support System (SPK), The Weighted Product (WP).